Comparison of alkali treatments for efficient release of p-coumaric acid and enzymatic saccharification of sorghum pith. (May 2016) - Jiang, Kankan; Li, Lulu; Long, Liangkun; Ding, Shaojun
Highlights: Sorghum pith was treated by NaOH for p -coumaric acid release and enzymatic saccharification. Strong linear correlation exists between p -coumaric acid release and enzymatic glucose yield. Desirable conditions were obtained at 37 °C for 12 h with 2% NaOH or 100 °C for 37 min with 1.75% NaOH. High enzymatic glucose and p -coumaric acid yields can be achieved under above conditions. Abstract: Two separate temperature and time ranges were respectively conducted for optimizing release of p -coumaric acid and enzymatic saccharification of sorghum pith by NaOH pretreatment using response surface methodology. Two desirable pretreatment conditions were selected as follows: 37 °C, 2% NaOH and 12 h, and 100 °C, 1.75% NaOH and 37 min in the low and high temperature ranges, respectively. Under these conditions, the enzymatic glucose yields were 85.6% and 90.4% respectively, whereas p -coumaric acid yields were 95.1% and 98.1% respectively. The final recovery of esterified p -coumaric acid reached 82.8% and 87.4% respectively after further separation with HP-20 resin. Interestingly, strong linear correlations exist between p -coumaric acid release with glucan saccharification yield and lignin dissolution. These results indicate that sorghum pith could be an attractive source for natural p -coumaric acid and efficient release of p -coumaric acid and enzymatic saccharification of sorghum pith can be achieved by mild NaOH pretreatment.